2022
DOI: 10.3390/jcm11195833
|View full text |Cite
|
Sign up to set email alerts
|

Diet, Digestion, and the Dietitian: A Survey of Clinicians’ Knowledge, Attitudes and Practices to Advance the Treatment of Gastrointestinal Disturbances in Individuals with Anorexia Nervosa

Abstract: Despite advances in treatment of anorexia nervosa (AN), current therapeutic approaches do not fully consider gastrointestinal disturbances (GID), often present in AN. Addressing GID, both symptoms and disorders, is likely to improve treatment adherence and outcomes in people with AN. GID are complex and are linked to a range of factors related to eating disorder symptomology and can be impacted by nutritional treatment. It is not known which dietetic practices are currently used to address GID in AN. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Finally, West et al [ 7 ] describe the range of gastrointestinal disturbances experienced by individuals with AN, and the scant literature regarding management and treatment of these issues by dietitians. Their study revealed that dietitians with a greater understanding of gastrointestinal disturbances in AN recognised its impact on the individual’s quality of life and were more likely to screen patients for such disturbances.…”
mentioning
confidence: 99%
“…Finally, West et al [ 7 ] describe the range of gastrointestinal disturbances experienced by individuals with AN, and the scant literature regarding management and treatment of these issues by dietitians. Their study revealed that dietitians with a greater understanding of gastrointestinal disturbances in AN recognised its impact on the individual’s quality of life and were more likely to screen patients for such disturbances.…”
mentioning
confidence: 99%